2018
DOI: 10.1097/ajp.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preoperative Radiologic Severity, Sensory Testing, and Temporal Summation on Chronic Postoperative Pain Following Total Knee Arthroplasty

Abstract: Objectives: Knee osteoarthritis (KOA) can be associated with local and central sensitization. As an indicator of the central gain, facilitated temporal summation of pain (TSP) has been found in KOA patients. This facilitation is predictive of the development of chronic postoperative pain after total knee arthroplasty (TKA). Other studies have suggested hypoesthesia/hypoalgesia to thermal stimuli as a feature in KOA. This study investigated associations between preoperative TSP, thermal sensitivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 45 publications
4
118
0
1
Order By: Relevance
“…Patients with musculoskeletal pain are often pain sensitive to pressure stimuli and not necessarily to heat stimuli (Neziri et al, ; Petersen, Simonsen, Laursen, & Arendt‐Nielsen, ). Offset analgesia can be evoked by heat (Grill & Coghill, ; Ligato et al, ; Petersen, Andersen, et al, ) and electrical stimuli (Petersen, Mørch, et al, ), but currently no study has demonstrated an offset analgesia effect using pressure stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with musculoskeletal pain are often pain sensitive to pressure stimuli and not necessarily to heat stimuli (Neziri et al, ; Petersen, Simonsen, Laursen, & Arendt‐Nielsen, ). Offset analgesia can be evoked by heat (Grill & Coghill, ; Ligato et al, ; Petersen, Andersen, et al, ) and electrical stimuli (Petersen, Mørch, et al, ), but currently no study has demonstrated an offset analgesia effect using pressure stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The VAS was anchored at 0 cm: no pain and 10 cm: worst pain imaginable. These assessments have been consistently used in similar studies [27,39,[41][42][43].…”
Section: Protocolmentioning
confidence: 99%
“…Further, mechanistic pain profiling of knee OA patients has found preoperative TSP and PPTs to be predictive of the development of chronic postoperative pain following total joint replacement [27,39,40,42,58]. These parameters are normalized after a successful TKA recovery leading to a painfree outcome [24,31] and this highlights the significance of such mechanisms as targets for pain management.…”
Section: Introductionmentioning
confidence: 99%
“…Several pre-and perioperative risk factors for chronic postoperative TKA have been suggested [4,5] where the major risk factors are preoperative, heightened, psychological factors related to pain (e.g. pain catastrophizing, anxiety, or depression) [6], high pre-and perioperative pain intensities [7][8][9] and more recently preoperative pain sensitivity [8,[10][11][12]. Gabapentinoids have an anxiolytic effect [13][14][15] and reduce neuronal hyperexcitability [16], and it has been suggested that preoperative and perioperative administration of gabapentinoids may reduce the incidence of chronic postoperative pain.…”
Section: Introductionmentioning
confidence: 99%
“…A measure of pain facilitation is temporal summation of pain (TSP), and gabapentin has been shown to decrease TSP in healthy subjects [16]. Preoperatively, facilitated TSP has been linked to the development of chronic postoperative pain following total hip arthroplasty surgery [10], TKA [8,11,12], and acute postoperative pain following thoracotomy [32], indicating that preoperative administration of gabapentinoids could potentially reduce the risk of developing chronic postoperative pain. Since, preoperative administration of pregabalin has been found to diminish neuropathic chronic postoperative pain following TKA [17], the current study hypothesized that different doses of gabapentin would reduce the prevalence of chronic postoperative pain following TKA and aimed to explore the effect of pre-and perioperatively administered gabapentin on the development of chronic postoperative pain in patients undergoing TKA.…”
Section: Introductionmentioning
confidence: 99%